Multi-bandgap quantum dots ensemble for near-infrared photovoltaics - Mahajan, Chandan; Dambhare, Neha V.; Biswas, Arindam; Sharma, Anjali; Shinde, Dipak Dattatray; Rath, Arup K. (Energy Technology, 2023)
Narrow bandgap quantum dots (QDs) are an important class of materials for near-infrared (NIR) optoelectronic devices owing to their size-tunable bandgap and chemical root processing. In photovoltaic applications, NIR QDs could be particularly useful to complement the sub-bandgap transmission loss of NIR solar radiation from perovskite and c-Si solar cells. However, insufficient carrier extraction thickness associated with the narrow NIR excitonic bandwidth of QDs limits the conversion efficacy of the broad NIR solar spectrum. Here, we utilize a multi-bandgap QD ensemble which widens the NIR absorption bandwidth to mimic the broad solar spectrum. A solution-phase ligand passivation strategy is used to control doping properties and energy level alignment of multi-bandgap QDs. We successfully developed bulk-heterojunction solar cells using the multi-bandgap QD ensemble, which yields higher carrier extraction thickness and broader NIR absorption. The gain from NIR absorption and carrier transport resulted in higher short-circuit current generation and power conversion efficiency (PCE) in solar cell devices. The champion device shows 8.73% PCE under 1.5 AM solar illumination and 7.44% and 5.05% PCE for the NIR photons transmitted from perovskite and c-Si layers.
Keywords: bulk-heterojunctions; multi-bandgap; near-infrared; quantum dots; solar cells; surface passivation

Magnetic chemiresistive Fe-doped In2O3 nanocubes to Tunably detect NO2 at ppm to ppb concentrations - Rudra, Pratyasha; Dambhare, Neha V.; Srihari, Velaga; Das, Sagnik; Rath, Arup Kumar; Saha, Debdulal; Mondal, Swastik (ACS APPLIED NANO MATERIALS, 2024)
Keywords: GAS-SENSING PROPERTIES; METAL-OXIDE NANOSTRUCTURES